2020
DOI: 10.1016/j.jid.2019.11.018
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule CCR2 Antagonist Depletes Tumor Macrophages and Synergizes with Anti–PD-1 in a Murine Model of Cutaneous T-Cell Lymphoma (CTCL)

Abstract: Tumor-associated macrophages (TAMs) recruited from blood monocytes are key in establishing an immunosuppressive tumor microenvironment (TME) for the support of tumor growth. We hypothesize that blocking monocyte trafficking (through the inhibition of specific chemokine receptors) into skin can positively affect tumor development. Herein, the authors examined the effects of oral administration of a small molecule inhibitor for CCR2, CCR2i, which blocks CCR2-mediated chemotaxis of monocytes in a syngeneic mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…In addition, bexarotene reduced the production of CCL22 from monocytes‐derived M2 macrophages in vitro, 5 whereas interferon‐α and interferon‐γ did not affect the production of CCL22 6 . In another report, Wu et al 7 reported that a CCR2 antagonist inhibited the recruitment of a TAM precursor and decreased TAM levels in the tumor microenvironment, leading to the suppression of tumor growth in a mouse MBL2/DNFB CTCL model. Moreover, the depletion of TAMs by clodronate‐containing liposomes suppressed tumor growth in a human CTCL xenograft model 8 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, bexarotene reduced the production of CCL22 from monocytes‐derived M2 macrophages in vitro, 5 whereas interferon‐α and interferon‐γ did not affect the production of CCL22 6 . In another report, Wu et al 7 reported that a CCR2 antagonist inhibited the recruitment of a TAM precursor and decreased TAM levels in the tumor microenvironment, leading to the suppression of tumor growth in a mouse MBL2/DNFB CTCL model. Moreover, the depletion of TAMs by clodronate‐containing liposomes suppressed tumor growth in a human CTCL xenograft model 8 .…”
Section: Discussionmentioning
confidence: 95%
“…Since most lymphoma cells in MF express CCR4, which plays crucial roles in the trafficking of CTCL cells to skin, 3 and since MF develops from patch and plaque stages to the tumor stage, 4 it is important for the development of treatments for MF to investigate the tumor microenvironment with a focus on chemokine production 3‐7 . Indeed, as we previously reported, TAMs in the lesional skin of MF produce various chemokines, 5,6 and they may be a target for anti‐CTCL therapy, such as bexarotene 5 and interferons 6 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Alternatively, targeting the CCL2/CCR2 axis, a key chemokine pathway involved in macrophage migration to inflammatory sites, to limit their entry into the TME enabled numerical and functional improvement of intratumoral lymphocyte infiltrate ( 26 29 ). Wu et al demonstrated improved survival outcomes in cutaneous T-cell lymphoma-bearing mice treated with a CCR2 inhibitor and anti-PD-1 ( 28 ). Collectively, these studies highlight that inhibition of pro-tumor TAMs in the TME reinvigorates the anti-PD-1-driven T cell response.…”
Section: Improving Tumor Control With Myeloid Cells In the Tmementioning
confidence: 99%
“…Therapeutically altering these immunomodulatory components may promote anti-tumor immunity either alone or synergize with FDA-approved immune checkpoint inhibition. enabled numerical and functional improvement of intratumoral lymphocyte infiltrate (26)(27)(28)(29). Wu et al demonstrated improved survival outcomes in cutaneous T-cell lymphoma-bearing mice treated with a CCR2 inhibitor and anti-PD-1 (28).…”
Section: Improving Tumor Control With Myeloid Cells In the Tmementioning
confidence: 99%